Social Identity Theory and Biblical Interpretation - Baker, Coleman A. (Biblical theology bulletin, 2012)
This study is intended to provide readers with an introduction to Social Identity Theory and its use as a heuristic device for biblical interpretation. After a general overview of Social Identity Theory and some important related concepts, the study summarizes some of the scholarly works that have employed this model in studies of Hebrew and Christian texts.